Content and Language Integrated Learning (CLIL): The Model of CLIL Suit to The Context of Aceh - muamar, m rezeki (JURNAL VARIASI, 2012)
The notion of combining content teaching and language learning has developed in Indonesia included Aceh since a decade ago. It shows from the increasing number of bilingual schools in Aceh. There is a number of CLIL models that can be adopted by the schools in Indonesia espesially Aceh. This paper discuss the models of CLIL that suit to the context of Indonesia especially Aceh. As English is a foreing language for the Achenesse, it is important to consider different models of CLIL for different level of schools. Integrated English to play-based activities is an effective model for pre-school students. While, Model A1 (Confidence-building and introduction to key concepts), B2 (Bilingual education), and C2 (Adjunct CLIL) are effective for primary schools, secondary schools, and tertiary respectively.